2018
DOI: 10.2147/cmar.s169222
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between <em>IGF2BP2</em> and <em>IGFBP3</em> polymorphisms and susceptibility to non-small-cell lung cancer: a case&ndash;control study in Eastern Chinese Han population

Abstract: BackgroundIGF2BP2 and IGFBP3 polymorphisms may be associated with cancer risk.MethodsWith an aim to determine the association of variations in IGF2BP2 and IGFBP3 genes with risk of non-small-cell lung cancer (NSCLC), IGF2BP2 rs1470579 A>C, rs4402960 G>T and IGFBP3 rs2270628 C>T, rs3110697 G>A, and rs6953668 G>A polymorphisms were selected and genotyped in 521 NSCLC patients and 1,030 controls.ResultsWe found that there was no difference in IGF2BP2 and IGFBP3 genotype distribution among the NSCLC patients and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
2
16
1
Order By: Relevance
“…The relationship between IGF2BP2 and PI3K/ Akt signaling pathway has been discussed, suggesting up-regulated IGF2BP2 in pancreatic cancer plays a role in cell proliferation [33]. In addition, SNPs of IGF2BP2 and IGF2BP3 has been proved to promote the lymph node metastasis of esophagogastric junction adenocarcinoma [34]. In our GO and KEGG analysis, we noticed that IGF2BP2-related module was correlated with central carbon metabolism, thyroid hormone synthesis and HIF-1signaling pathway, which provided some potential regulatory metabolism of m 6 A RNA modification.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between IGF2BP2 and PI3K/ Akt signaling pathway has been discussed, suggesting up-regulated IGF2BP2 in pancreatic cancer plays a role in cell proliferation [33]. In addition, SNPs of IGF2BP2 and IGF2BP3 has been proved to promote the lymph node metastasis of esophagogastric junction adenocarcinoma [34]. In our GO and KEGG analysis, we noticed that IGF2BP2-related module was correlated with central carbon metabolism, thyroid hormone synthesis and HIF-1signaling pathway, which provided some potential regulatory metabolism of m 6 A RNA modification.…”
Section: Discussionmentioning
confidence: 99%
“…Values represent the mean ± SD of three independent experiments. *P < 0.05; **P < 0.01. lung cancer 33,34 . Previous studies have reported that IGFBP3 expression is increased in many tumors with metastasis, including lung cancer and oral cancer 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP3 also exhibits IGF-independent effects. Previous studies have shown that IGFBP3 expression is correlated with various cancers, such as esophageal cancer 24 , 25 , gastric cancer 26 , colorectal cancer 27 , 28 , pancreatic cancer 29 , prostate cancer 30 32 , and lung cancer 33 , 34 . Previous studies have reported that IGFBP3 expression is increased in many tumors with metastasis, including lung cancer and oral cancer 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…M6A-RNA methylation refers to methylation of adenosine bases at position N6 in 3′UTRs near the stop codons but within the internal long exons [ 10 , 11 ]. Modified IGF2BP2 participates in the development and progression of multiple metabolic disease and cancers, including diabetes [ 2 ], obesity [ 12 ], fatty liver [ 13 ], breast cancer [ 14 ], colorectal carcinoma [ 15 ], esophageal adenocarcinoma [ 16 ], glioma [ 17 ], hepatocellular carcinoma [ 18 ], lung cancer [ 19 ], pancreatic cancer [ 20 ] and many others.…”
Section: Introductionmentioning
confidence: 99%